Metabolic Contributions of an Alphaproteobacterial Endosymbiont in the Apicomplexan Cardiosporidium cionae - Hunter, Elizabeth Sage; Paight, Christopher; Lane, Christopher E. (Frontiers in Microbiology, 2020)
Apicomplexa is a diverse protistan phylum composed almost exclusively of metazoan-infecting parasites, including the causative agents of malaria, cryptosporidiosis, and toxoplasmosis. A single apicomplexan genus, Nephromyces, was described in 2010 as a mutualist partner to its tunicate host. Here we present genomic and transcriptomic data from the parasitic sister species to this mutualist, Cardiosporidium cionae, and its associated bacterial endosymbiont. Cardiosporidium cionae and Nephromyces both infect tunicate hosts, localize to similar organs within these hosts, and maintain bacterial endosymbionts. Though many other protists are known to harbor bacterial endosymbionts, these associations are completely unknown in Apicomplexa outside of the Nephromycidae clade. Our data indicate that a vertically transmitted 𝝰-proteobacteria has been retained in each lineage since Nephromyces and Cardiosporidium diverged. This 𝝰-proteobacterial endosymbiont has highly reduced metabolic capabilities, but contributes the essential amino acid lysine, and essential cofactor lipoic acid to C. cionae. This partnership likely reduces resource competition with the tunicate host. However, our data indicate that the contribution of the single 𝝰-proteobacterial endosymbiont in C. cionae is minimal compared to the three taxa of endosymbionts present in the Nephromyces system, and is a potential explanation for the virulence disparity between these lineages.